Viability droplet digital polymerase chain reaction accurately enumerates probiotics and provides insight into damage experienced during storage - Kiefer, Anthony; Byrd, Phillip M.; Tang, Peipei; Jones, Gregory; Galles, Kevin; Fallico, Vincenzo; Wong, Connie (Frontiers in Microbiology, 2022)
Probiotics are typically enumerated by agar plate counting (PC) techniques. PC has several limitations including poor specificity, high variability, inability to enumerate dead cells, viable but non-culturable cells and cells in complex matrices. Viability droplet digital polymerase chain reaction (v-ddPCR) is an emerging technique for enumerating probiotics with improved specificity, precision, and the ability to enumerate cells in varying states of culturability or in complex matrices. Good correlation and agreement between v-ddPCR and PC is well documented, but not much research has been published on the comparison when enumerating freeze-dried (FD) probiotics during storage. In this study, v-ddPCR utilizing PE51 (PE51-ddPCR), a combination of propidium monoazide (PMA) and ethidium monoazide (EMA), was evaluated as alternative enumeration technique to PC on blends of four FD probiotic strains over the course of a 3-month storage study with accelerated conditions. When PMA and EMA are combined (PE51), this study demonstrates agreement (bias = 7.63e +9, LOA = 4.38e +10 to 5.9e +10) and association (r = 0.762) between PC and v-ddPCR, at or above levels of an accepted alternative method. Additionally, v-ddPCR with individual dyes PMA and EMA provide insight into how they individually contribute to the viable counts obtained by PE51-ddPCR and provide a more specific physiological understanding of how probiotics cope with or experience damage during storage.